The Role of Emotion Regulation in Video Gaming and Gambling Disorder: A Systematic Review. Issue 4 (December 2019) - Marchica, Loredana A.; Mills, Devin J.; Derevensky, Jeffrey L.; Montreuil, Tina C.
Abstract : ABSTRACT: Behavioral addictions are now recognized as a psychiatric condition. With this recognition came increased research interest, specifically within the video gaming and gambling fields, into the etiology and symptomology of these behavioral addictions. Emotion regulation (ER) has significant implications for mental health, with research highlighting the link between ER and the development of psychopathology. However, the relationship between ER and behavioral addictions remains relatively unknown. Objectives: This review investigated the recent literature on this relationship. Methods: Out of an initial sample of 2471 studies, 20 were eligible for inclusion. Data regarding outcome measures, sampling methods, results, and effect sizes of relationships were extracted and critically evaluated. Results: Results indicated 90% of studies found lower ER to be associated with reports of greater video gaming or gambling disorder symptomology, with 13 studies (65%) reporting medium to large effect sizes. Conclusion: The findings provide an in-depth analysis of the relationship between ER and behavioral addictions and highlights the key role ER plays in these addictive behaviors. This review provides novel insights into the potential prevention and intervention practices for behavioral addictions as well as recommendations for future directions. Abstract : N/A: Les dépendances comportementales sont maintenant reconnues comme une situation psychiatrique. Cette reconnaissance a entraîné un intérêt accru pour la recherche, en particulier dans les domaines du jeu vidéo et du jeu, dans l'étiologie et la symptomologie de ces dépendances comportementales. La régulation des émotions (RE) a des implications importantes au niveau de la santé mentale, les recherches soulignant le lien entre la RE et le développement de la psychopathologie. Cependant, la relation entre la RE et les dépendances comportementales reste relativement inconnue. Objectifs: Cette étude a examiné la littérature récente concernant cette relation. Méthodes: Sur un échantillon initial de 2 471 études, 20 étaient éligibles pour l'inclusion. Les données concernant les mesures de résultats, les méthodes d'échantillonnage, les résultats et l'ampleur de l'effet des relations ont été extraites et évaluées de manière critique. Résultats: Les résultats ont indiqué que 90% des études démontrent que la baisse de la RE était associée à des rapports faisant état d'une plus grande symptomatologie du jeu vidéo, 13 études (65%) rapportant des effets de taille moyenne à grande. Conclusions: Les résultats fournissent une analyse approfondie de la relation entre la RE et les dépendances comportementales et mettent en évidence le rôle clé que la RE joue dans ces dépendances comportementales. Cette étude fournit de nouvelles informations sur les pratiques potentielles de prévention et d'intervention pour les dépendances comportementales ainsi que des recommandations pour des orientations futures.